FINITE ELEMENT ANALYSIS OF PISTON HEAD USING CAD - Nitin K.S; Sahani Sahani; S.B. Lai (Nusa Putra University, 2018)
The motive of undertaking this project of structural analysis of piston head is to study and evaluate the performance in real working conditions of the piston in internal combustion engine. In this paper, the work is carried out to measure the stress distribution on the top surface of the piston made up of aluminium alloy. In IC engine piston experiences uneven temperature distribution and from piston head to skirt. The analysis predicts that due to stress generated the top surface of the piston may be damage or break during the operating conditions, since the damaged or broken parts are so expensive to replace and generally are not easily available, the 3D model of piston is created using Creo. 3D model is imported to the Abaqus and FEA is performed. By identifying the true design features, the extended service life and long term stability is assured.